2017
DOI: 10.1016/j.nucengdes.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

On the use of (U)RANS and LES approaches for turbulent incompressible single phase flows in nuclear engineering applications

Abstract: The present paper gives some ideas and guidelines one should keep in mind while running (U)RANS or LES computations. The paper starts with (U)RANS approaches, advocating the use of Reynolds Stress Models for complex flows and recommending further work on modeling of turbulent heat fluxes, which remains today too basic in industry. The superiority of wallresolved models vs. wall-modeled in RANS is recalled and the use of adaptive wall treatment is suggested. The concept of Unsteady RANS is finally questioned. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Pseudo-2D calculations [6] have been performed with the commercial finite volume code STAR-CCM+ [1] to estimate the Taylor microscale (𝜆 = √ ). The results have been used to design the LES and DNS numerical experiments performed with Nek5000 [7]. The DNS mesh has been designed such that the distance between Gauss-Lobatto-Legendre (GLL) points is smaller than min( 𝜆 2 ,η).…”
Section: Advanced Rans Computation Star-ccm+mentioning
confidence: 99%
“…Pseudo-2D calculations [6] have been performed with the commercial finite volume code STAR-CCM+ [1] to estimate the Taylor microscale (𝜆 = √ ). The results have been used to design the LES and DNS numerical experiments performed with Nek5000 [7]. The DNS mesh has been designed such that the distance between Gauss-Lobatto-Legendre (GLL) points is smaller than min( 𝜆 2 ,η).…”
Section: Advanced Rans Computation Star-ccm+mentioning
confidence: 99%
“…In order to perform industrial and affordable computations, wall-modeled LES is used, especially by EDF and CEA (see below for the particular case of Framatome). This approach might give correct mean values (see Benhamadouche [13]). However, its use is still subject to discussion and objections (see Piomelli [14]) and this approach using wall functions concepts can also be seen as a very first step of hybrid RANS/LES technique (using a logarithmic profile for example).…”
Section: Computational Domain and Boundary Conditionsmentioning
confidence: 99%
“…The study demonstrated that CFD could provide accurate and reliable predictions of fluid flow and heat transfer in complex geometries and for non-Newtonian fluids. In addition, CFD has been used to study single-phase flows in nuclear engineering applications using both Unsteady Reynolds Average Navier-Stokes (URANS) and Large Eddy Simulation (LES) approaches [4]. The authors reviewed the use of URANS and LES approaches for turbulent incompressible single-phase flows in nuclear engineering applications.…”
Section: Introductionmentioning
confidence: 99%